Diffusion and solid state reactions in Fe/Ag/Pt and FePt/Ag thin-film systems. (27th March 2015) - Katona, G L; Safonova, N Y; Ganss, F; Mitin, D; Vladymyrskyi, I A; Sidorenko, S I; Makogon, Iu N; Beddies, G; Albrecht, M; Beke, D L
Abstract: Depth profiles of tri-layered Fe(15 nm)/Ag(10 nm)/Pt(15 nm)/SiO2 (100 nm)/Si(1 0 0) and bi-layered Fe50 Pt50 (15 nm)/Ag(7.5 nm)/SiO2 (100 nm)/Si(1 0 0) thin films after different heat treatments were investigated by secondary neutral mass spectrometry. Isotherm annealing of the tri-layered samples was carried out between 245 and 390 °C up to several hours, while isochrone thermal annealing was performed between 600 and 900 °C for 30 s. Composition profiles, obtained after isotherm heat treatment, show that initially there was a strong intermixing between Ag and Pt, resulting most likely in the formation of an Ag x Pt1− x reaction layer. Furthermore, the intermixing process was much faster in the Ag layer accompanied by the segregation of Ag to the substrate/Pt interface. Later on the Pt, which diffused through the Ag layer, started to penetrate into the Fe grain boundaries. This process led to the formation of the FePt reaction product. At the same time as the Pt diffused into the Fe layer, reducing the amount of Pt in the Ag x Pt1− x layer, the Ag appeared to 'move' towards the substrate. Finally, an almost fully homogeneous FePt alloy layer formed with some FePt present in the grain boundaries of the remaining Ag. This behavior was compared to both types of samples subjected to isochrone thermal annealing. High temperature treatments resulted in similar results and eventually in the formation of a homogeneous L10 ordered FePt alloy with randomly distributed Ag in the grain boundaries and at the free surface.